2020
DOI: 10.1017/s135246582000017x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of safety behaviour use on cognitive, psychophysiological, emotional and behavioural responses during a speech task

Abstract: Background: There is a debate among researchers and clinicians regarding whether the judicious use of safety behaviours (SBs) during exposure therapy is helpful or detrimental. Central to this debate is the premise that SBs may interfere with one’s ability to gather disconfirmatory evidence. Aims: No study to date has assessed how SB use may impact cognitive mechanisms implicated during an exposure-like task. We investigated multiple cognitive, emotional, psychophysiological and behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
(64 reference statements)
3
9
0
Order By: Relevance
“…Therefore, it may not be so much about exactly how we prepare clients for exposure therapy, but rather, what the experience is actually like for them. Consistent with our previous suggestion (Tutino et al, 2020), we contend that people believe that SBs are more helpful than they actually experience them to be. Conversely, researchers previously found that individuals with high social anxiety may indeed be aware that SBs are counterproductive, and worry that others (i.e., audience members) evaluate them negatively as a result (Vassilopoulos, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Therefore, it may not be so much about exactly how we prepare clients for exposure therapy, but rather, what the experience is actually like for them. Consistent with our previous suggestion (Tutino et al, 2020), we contend that people believe that SBs are more helpful than they actually experience them to be. Conversely, researchers previously found that individuals with high social anxiety may indeed be aware that SBs are counterproductive, and worry that others (i.e., audience members) evaluate them negatively as a result (Vassilopoulos, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…In this modified version, all items were modified to the past tense (e.g., "I got tongue-tied"). In our previous study (Tutino et al, 2020), modified SATI scores demonstrated excellent internal consistency at Time 1 (a ¼ .94 and Time 2; a ¼ .97).…”
Section: Social Phobia Inventory (Spin)mentioning
confidence: 70%
See 3 more Smart Citations